DEVELOPMENT OF BAMBOO YOGYAKARTA VILLAGE TOURISM USING LOCALISM APPROACH - Nadya, Eva Ayu; Winarto, Erwin Djuni (Border: Jurnal Arsitektur, 2019)
Sleman Regency, has a tourism potential that is high enough if optimized can provide a positive influence on the surrounding community. One of the tourist villages that has potential in Ds. Sendangagung Dsn. Brajan, Kec. Step aside. To produce tourism that is of interest to tourists, it is necessary to develop tourist facilities, namely: 1) Lodging that until now still uses the homes of local residents; 2) Bamboo Classes for Packages for Existence of Learning Bamboo Crafts; 3) Performance area as a place for performing dance and gamelan performances; 4) Bamboo Art Gallery and 5) Bamboo Shop as a container for handicrafts by craftsmen and visitors of tourist villages. The location of the site is an empty land area of approximately 20,000m². From several facts, the issues and goals that have been analyzed appear a red thread which is then used as the design theme, "When Nature Meet Art". The intention is to express the identity of the natural beauty of the Brajan Bamboo Tourism Village and the bamboo handicrafts produced. The design approach uses Localism to manifest buildings towards the environment in the realm of tradition, culture & social. So that the resulting design is able to realize a tourist area that is able to synergize between buildings with natural, cultural, and local wisdom comprehensively.